2012
DOI: 10.1093/bja/aer502
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of cranial spread during caudal blockade in children: effect of the speed of injection of local anaesthetics

Abstract: The main finding of the present study is that the speed of injection of the local anaesthetic does not affect its cranial spread during caudal blockade in infants and children. Therefore, the prediction of the cranial spread of the local anaesthetic, depending on the injection speed, is not possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…18,19 Postinjection (when the X-ray image was obtained), the caudal solution may still be creeping cranially and not yet has reached its highest level and there may be 'pharmacological spread' that is not visible to the naked eye on X-ray examination. 20 Our results also demonstrated that there were no differences in vital parameters like heart rate and blood pressure between the two groups despite the significantly higher spread level of the HVLC compared with the LVHC. The mechanism for this lack of hemodynamic sympathectomy was postulated to be the immaturity of the sympathetic nerve system.…”
Section: Discussionsupporting
confidence: 56%
“…18,19 Postinjection (when the X-ray image was obtained), the caudal solution may still be creeping cranially and not yet has reached its highest level and there may be 'pharmacological spread' that is not visible to the naked eye on X-ray examination. 20 Our results also demonstrated that there were no differences in vital parameters like heart rate and blood pressure between the two groups despite the significantly higher spread level of the HVLC compared with the LVHC. The mechanism for this lack of hemodynamic sympathectomy was postulated to be the immaturity of the sympathetic nerve system.…”
Section: Discussionsupporting
confidence: 56%
“…A (prediction of epidural depth) Local anesthetic spread Brenner et al, 27 Lundblad et al, 35 Triffterer et al, 30 Tsui et al, 37 Ueda et al 39…”
Section: Ib (Prediction Of Epidural Depth)mentioning
confidence: 99%
“…27,30,35,37,39 Brenner et al 27 used ultrasound to show correlations between injectate volume (0.7, 1.0, or 1.3 mL/kg) and cranial spread during caudal blockade. There were significant positive correlations between 1.3 mL/kg and 0.7 mL/kg (P = 0.0002) as well as 1.3 mL/kg and 1.0 mL/kg (P = 0.03); however, the observed differences were small and did not allow for a reasonable prediction of a volume-cranial extension relationship.…”
Section: Neuraxial Anesthesiamentioning
confidence: 99%
“…studied the effect of the speed of injection of the local anesthetic in the primary spread of the drug. [10] Although their study did not yield any significant effect, we tried to keep the speed constant using an infusion pump.…”
Section: Discussionmentioning
confidence: 99%